Україна в європейських історичних процесах. Рецензія на рукопис монографії: Україна в історії Європи ХІХ – початку ХХІ століття. Історичні нариси / під ред. С. В. Віднянського. – К.: Інститут історії України НАН України, 2020. – 447 с. - Машевський, Олег Петрович (Київський національний університет імені Тараса Шевченка, 2020)
The chronological boundaries of the collective monograph cover a long historical period, which extends to the era of European Modernism and continues to the modern (current) history of European Postmodernism. The key thesis of the team of authors of the monograph is the idea of systemic belonging of Ukraine to European civilization as its component, which interacts with other parts of the system. The first chapter of the peer-reviewed collective monograph "European receptions of Ukraine in the XIX century" shows the reflection of the Ukrainian problem in the German-language literature of the first half of the XIX century, taking into account new archival document, the development of Ukraine's relations with other Slavic peoples is traced, and the peculiarities of Ukrainian-Bulgarian relations are considered as a separate case study. An interesting paragraph of the collective monograph devoted to cultural, educational and scientific cooperation of Dnieper Ukraine with European countries. This information illustrates well how the Industrial Revolution radically changed the face of the planet, brought new scientific experience that gave room for the development of the capitalist system, and with them, the Industrial Revolution brought social problems, environmental disasters that still cannot be solved. Thomas Malthus (1766-1834) formulated the "iron law of wages", according to which workers can receive only a living wage. The second chapter of the collective monograph "The Ukrainian Question and Ukraine in the European History of the Twentieth Century" presents an integrated narrative of Ukrainian national history in the light of the European history of the two world wars and their consequences. The First World War, or the Great War, undoubtedly became a turning point in European history and, accordingly, in the national histories of European countries. The historical experience of the Ukrainian national liberation struggle of the Ukrainian people for the right to European development is covered in the paragraph of the collective monograph "Ukrainian Diplomatic Service 1917-1924". The vicissitudes of Stalin's industrialization and collectivization and their impact on the Ukrainian SSR's relations with European states in the 1920s and 1930s are highlighted in terms of continuity of ties with Europe. A separate regional example of the situation is covered on the example of the history of Transcarpathia on the eve of World War II. The third chapter of the collective monograph "Independent Ukraine in the European integration space" highlights the features of Ukraine's current positioning in Europe. After the collapse of the USSR, ideological obstacles to the development of globalization were overcome. The American political scientist F. Fukuyama in his work "The End of History" concluded the final victory of liberal ideology. This section of the peer-reviewed collective monograph also highlights the position of the international community on the Crimean referendum in 2014, analyzes the policy of Western European countries on the Ukrainian-Russian armed conflict on the example of the policy of Germany, France and Austria. The research result is a separate model of reality, which is reproduced with the help of a certain perception and awareness of the historian. In this sense, the author's team of the monograph has achieved the goal of creating a meaningful narrative that highlights the place of Ukraine at different stages of modern and postmodern European history. From the point of view of the general perception of the narrative offered to the reader, the authors of the collective monograph managed to harmonize individual stylistic features in a conceptually unified text, the meanings of which will be interesting to both professional historians and students and the general readership.

Хронологічні межі колективної монографії охоплюють тривалий історичний період, що поширюється на епоху єв ропейського модерну і триває до сучасної (поточної) історії європейського постмодерну. Ключовою тезою колективу авторів монографії є ідея системної належності України до європейської цивілізації як її складової частини, що взаємодіє з іншими частинами системи. У першому розділі рецензованої колективної монографії "Європейські рецепції України в ХІХ столітті" показано віддзеркалення української проблеми в німецькомовній літературі першої половини ХІХ ст., з урахуванням нових архівних документів простежено розвиток зв'язків України з іншими слов'янськими народами, як окреме кейс-стаді розглянуто особливості українсько-болгарські відносини. Цікавим є параграф колективної монографії, присвячений культурно-освітній і науковій співпраці Наддніпрянської України з європейськими країнами. Наведена інформація добре ілюструє, яким чином промислова революція докорінно змінила обличчя планети, принесла новий науковий досвід, що дав простір для розвитку капіталістичної системи, а разом з ними промислова революції привнесла соціальні проблеми, екологічні біди, які не вдається розв'я зати й досі. Томас Мальтус (1766–1834) сформулював "залізний закон зарплати", за яким робітники можуть одержувати лише прожитковий мінімум. Другий розділ колективної монографії "Українське питання та Україна в європейській історії ХХ століття" подає інтегрований наратив української національної історії у призмі європейської історії двох світових війн та їхніх наслідків. Перша світова війна, або Велика війна, безперечно, стала поворотною епохою європейської історії і, відповідно, національних історій європейських країн. Історичний досвід української національно-визвольної боротьби українського народу за здобуття права на європейський розвиток висвітлений у параграфі колективної монографії "Українська дипломатична служба 1917–1924 рр.". Перипетії сталінської індустріалізації і колективізації та їхній вплив на відносини УРСР з європейськими державами у 1920–1930-ті рр. висвітлені з погляду безперервності зв'язків із Європою. Окремий регіональний зразок ситуації подано на прикладі історії Закарпаття напередодні Другої світової війни. У третьому розділі колективної монографії "Незалежна Україна в європейському інтеграційному просторі" висвітлено особливості сучасного позиціонування України в Європі. Після розпаду СРСР ідеологічні перешкоди на шляху розвитку процесу глобалізації були подолані. Американський політолог Ф. Фукуяма у праці "Кінець історії" зробив висновок про остаточну перемогу ліберальної ідеології. У цьому розділі рецензованої колективної монографії також висвітлено позицію міжнародного співтовариства щодо кримського референдуму 2014 р., проаналізовано на прикладі політки ФРН, Франції, Австрії курс західноєвропейських країн ЄС щодо українсько-російського збройного конфлікту. Дослідницький результат є окремою моделлю реальності, що відтворена за допомогою певного сприйняття й обізнаності історика. У цьому сенсі авторський колектив монографії досягнув мети створення вагомого наративу, що висвітлює місце України на різних етапах модерної і постмодерної європейської історії. Із точки зору загального сприйняття запропонованого читачу наративу, авторам колективної монографії вдалося гармонізувати індивідуальні стилістичні особливості у концептуально єдиному тексті, смисли якого будуть цікавими як фаховим історикам та студентам, так і широкому читацькому колу.
Ukraine in European Historical Processes. Review of the Monograph Manuscript: Vidnianskyi, S. (Ed.). (2020). Ukraine in the History of Europe of the 19th – Early 21st Century: Historical Essays. A Monograph. Kyiv: Institute of History of Ukraine of the National Academy of Sciences of Ukraine
Keywords: Україна; європейська історія; колективна монографія; міжнародні відносини; Ukraine; European history; collective monograph; international relations